Quantitative ELISA analysis of protein expression in HepG2 cells following treatment with insulin, glucose, and bis(maltolato)oxovanadium(IV) - Al-Qatati, Abeer Samih (Penerbit Universiti Kebangsaan Malaysia, 2025)
Type 2 diabetes, the most common form of diabetes mellitus, is caused by insulin resistance. Many studies have sought orally active therapeutic compounds to replace insulin injections. This study examines the expression levels of key proteins involved in the insulin receptor (InsR) and AMP-activated protein kinase (AMPK) signaling pathways in HepG2 cells using ELISA, following treatment with insulin, glucose, and/or bis(maltolato)oxovanadium(IV) (BMOV). Treatment with BMOV for 24 h in the presence of glucose significantly increased the levels of glucose transporter type 4 (GLUT4) in the cell lysate from 511 ± 7 ng/L (control) to 882 ± 5 ng/L, and AMPK α1 in the supernatant from 683 ± 9 ng/L to 789 ± 6 ng/L. BMOV treatment for 1 h with glucose increased InsR levels in the lysate from 1.52 ± 0.11 ng/L to 4.01 ± 0.03 ng/L. Additionally, cell-based ELISA showed that AMPK β1 absorbance increased significantly under glucose + BMOV (1 h) treatment (1.32 ± 0.04) compared to the control (0.83 ± 0.03). These findings suggest that BMOV modulates glucose-related signaling pathways and may target the AMPK system - a major therapeutic axis for obesity, diabetes, and metabolic syndrome.